2009
DOI: 10.1136/bmj.b845
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and alcohol misuse

Abstract: How does alcohol misuse affect pregnancy and babies’ outcomes, and how is the problem managed in pregnant women?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Drinking alcohol during pregnancy also has known adverse effects such as increased risks of spontaneous abortion, premature birth, low birth weight, foetal death and foetal alcohol spectrum disorder, including foetal alcohol syndrome 36,56,61 . Given the available data on alcohol, fertility and pregnancy, as well as the fact that the foetus is most vulnerable to the effects of alcohol exposure during the first weeks after conception, when a woman may not even be aware she is pregnant, 65,66 the latest recommendation is that people trying for conception avoid consuming alcohol altogether and that the woman continues to abstain from alcohol during pregnancy 2,5,31,33,35,36,54,67–70 …”
mentioning
confidence: 99%
“…Drinking alcohol during pregnancy also has known adverse effects such as increased risks of spontaneous abortion, premature birth, low birth weight, foetal death and foetal alcohol spectrum disorder, including foetal alcohol syndrome 36,56,61 . Given the available data on alcohol, fertility and pregnancy, as well as the fact that the foetus is most vulnerable to the effects of alcohol exposure during the first weeks after conception, when a woman may not even be aware she is pregnant, 65,66 the latest recommendation is that people trying for conception avoid consuming alcohol altogether and that the woman continues to abstain from alcohol during pregnancy 2,5,31,33,35,36,54,67–70 …”
mentioning
confidence: 99%
“…Problematic drinking can cause sexual and reproductive health problems including infertility and miscarriage (Poole & Dell, 2005, Homan et al, 2007, Royal College of Obstetricians & Gynaecologists, 2006, Guerrini et al, 2009. Studies have also found that even moderate amounts of alcohol, for example fewer than eight drinks per week, can affect a woman's menstrual cycle and her fertility, and can increase the risk of miscarriage (Institute of Alcohol Studies, 2008, Jensen et al, 1998, Hakim et al, 1998, Guerrini et al, 2009. These findings have been disputed, however, and further research in the area is needed (Mette et al, 2002, Gill, 2000.…”
Section: Fertilitymentioning
confidence: 99%
“…Alcohol use during pregnancy can have potentially damaging effects on brain development in the foetus, and high intakes of alcohol have been strongly associated with congenital birth defects (teratogenesis) (Whittaker, 2003, Guerrini et al, 2009. The umbrella term used to describe the effects of heavy alcohol use during pregnancy is Foetal Alcohol Spectrum Disorders (FASD).…”
Section: Drinking During Pregnancymentioning
confidence: 99%
See 2 more Smart Citations